2019
DOI: 10.1038/s41398-018-0349-6
|View full text |Cite
|
Sign up to set email alerts
|

Can targeted metabolomics predict depression recovery? Results from the CO-MED trial

Abstract: Metabolomics is a developing and promising tool for exploring molecular pathways underlying symptoms of depression and predicting depression recovery. The AbsoluteIDQ™ p180 kit was used to investigate whether plasma metabolites (sphingomyelins, lysophosphatidylcholines, phosphatidylcholines, and acylcarnitines) from a subset of participants in the Combining Medications to Enhance Depression Outcomes (CO-MED) trial could act as predictors or biologic correlates of depression recovery. Participants in this trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…Previous studies in humans looked at a wide array of blood metabolites including lipids, AA, hormones, and biogenic amines to predict patient response to drug therapy [3]. More specifically, metabolomics has been applied following treatments with specific antidepressants, including sertraline [83], escitalopram [84], ketamine, and esketamine [84], as well as combinations of antidepressants (bupropion-escitalopram combination, venlafaxine-mirtazapine combination [85]). However, despite these studies already conducted in humans, animal models offer further important insights into the study of the therapeutic actions of drugs, thereby facilitating the development of novel treatments.…”
Section: Antidepressantsmentioning
confidence: 99%
“…Previous studies in humans looked at a wide array of blood metabolites including lipids, AA, hormones, and biogenic amines to predict patient response to drug therapy [3]. More specifically, metabolomics has been applied following treatments with specific antidepressants, including sertraline [83], escitalopram [84], ketamine, and esketamine [84], as well as combinations of antidepressants (bupropion-escitalopram combination, venlafaxine-mirtazapine combination [85]). However, despite these studies already conducted in humans, animal models offer further important insights into the study of the therapeutic actions of drugs, thereby facilitating the development of novel treatments.…”
Section: Antidepressantsmentioning
confidence: 99%
“…A recent meta-analysis [86] found strong associations between lipid metabolites and the prevalence of a depressive state. In fact, there are studies that suggest that the presence of certain metabolic markers can be used to predict both the propensity to develop depression [87], as well as the ability of patients taking anti-depression medications to demonstrate recovery [88]. Another group found that there were significant differences in the parts of the metabolomic profile associated with energy metabolism in the brain that could be linked, along with protein changes, to major depressive disorders [89].…”
Section: Extrinsic Factorsmentioning
confidence: 99%
“…To address this limitation, recent machine‐learning approaches have used genomics and/or metabolomics data to predict SSRI response, with AUC values of 0.68–0.78 . Although the studies demonstrated the feasibility of integrating biological factors with machine learning to achieve improved prediction performance, they were limited by lack of replication across multiple trials and multiple depression rating scales, in addition to lack of significance from a pharmacogenomics perspective …”
mentioning
confidence: 99%
“…[8][9][10] Although the studies demonstrated the feasibility of integrating biological factors with machine learning to achieve improved prediction performance, they were limited by lack of replication across multiple trials and multiple depression rating scales, in addition to lack of significance from a pharmacogenomics perspective. [8][9][10][11] In the present study, we used a machine-learning workflow (depicted schematically in Figure 1) to study the capabilities of Figure 1 The two-stage analysis workflow. Our analysis workflow proceeded in two stages.…”
mentioning
confidence: 99%
See 1 more Smart Citation